Who am I tomorrow? Chiharu Shiota - Wagner, Sina 1985- (Verlag für moderne Kunst, 2023)
Chiharu Shiota’s site-specific installation with the evocative title "Who am I Tomorrow?" at the former assembly hall of Kunstraum Dornbirn unfolds the fascinating impression of a living, oversized and independent organism. It seems to hover above the visitors, precisely fitted into the protective historical architecture, connected to it by an uncountable number of red connecting lines. Shiota here turns the inside out. The representability of the inner, of psychological states – experiences, traumas, fears, blows of fate or moments of happiness, a sense of security or social mortification – finds its correspondence in the giving of artistic form. In this, the personal, the intimate, intertwines with the public. For Shiota, her art is a home, a medium of communication with the world. And she constantly creates this sense from within herself, taking her own experiences as her impetus and subject. For almost three decades, she has been developing a consistent, highly aesthetic and internationally successful formal language